Viral Iced Tea Vendor Sunhaji Content and Poverty Commodification through Media Framing on Digital Platforms - Zulzilah, Siti; R.S.P.K.M. Isa, John; Mirzaev, Temur (Universitas Islam Negeri Raden Intan Lampung, 2025)
The viral phenomenon of poverty content on social media indicates a commodification practice that exploits vulnerability narratives as a new economic resource. This study aims to analyze how poverty is framed in the viral content of Mr. Sunhaji's iced tea vendors circulating on TikTok and YouTube, and how the process of commodification is interpreted in the production and circulation of this content. The research uses a qualitative approach with Robert Entman's framing analysis and Vincent Mosco's political economy of media perspective. Data was collected through content observation, documentation, and tracking online interactions from December 2024 to March 2025. The research findings indicate that poverty is constructed through the frames of empathy, injustice, and inspiration, which simultaneously strengthen the emotional appeal to drive engagement. This narrative was then commodified through content monetization by creators, increased visibility by the media, and expanded public participation in the form of donations and content reuse. The findings indicate that digital platforms transform representations of poverty into commodities that generate symbolic and material economic benefits and the need for critical media literacy regarding the practice of commodifying vulnerability in the digital ecosystem.